An autoregressive cross-lagged model unraveling co-occurring stimulant use and HIV: Results from a randomized controlled trial. (1st August 2021) - Lee, Ji-Young; Lee, Jae Eun; Moskowitz, Judith T.; Feaster, Daniel J.; Neilands, Torsten B.; Dilworth, Samantha E.; Rodriguez, Allan; Carrico, Adam W.
Highlights: Higher positive affect predicts significantly lower stimulant use after CM. Decreased stimulant use independently predicts long term reductions in viral load. Durable reductions in stimulant use should be used as a primary treatment target. Abstract: Background: Evidence-based interventions are needed to address the use of stimulants such as methamphetamine as a driver of onward HIV transmission and faster clinical HIV progression among sexual minority men. Prior randomized controlled trials with people living with HIV who use substances indicate that financial incentives provided during contingency management (CM) are effective for achieving short-term reductions in stimulant use and HIV viral load. However, the benefits of CM are often not maintained after financial incentives for behavior change end. Purpose: Data from a recently completed randomized controlled trial with 110 sexual minority men living with HIV who use methamphetamine was leveraged to examine mediators of the efficacy of a positive affect intervention for extending the benefits of CM. Methods: An autoregressive cross-lagged model was fit to determine if reductions in HIV viral load were mediated by intervention-related increases in positive affect and decreases in stimulant use measured in four waves over 15 months. Results: Higher baseline positive affect predicted significantly lower self-reported stimulant use immediately following the 3-month CM intervention period, even after controlling for self-reported stimulant use at baseline. Moreover, decreased stimulant use emerged as an independent predictor of long-term reductions HIV viral load at 15 months, even after adjusting for HIV viral load at baseline and the residual effect of the positive affect intervention. Conclusions: Findings underscore the importance of durable reductions in stimulant use as a primary intervention target that is essential for optimizing the clinical and public health benefits of HIV treatment as prevention.